Assessment of Dental Fear and Anxiety in Children Undergoing Nitrous Oxide-Oxygen Inhalation Sedation visiting BPKIHS - Birajee, Gajendra; Koirala, Bandana; Bhattarai, Balkrishna; Dali, Mamta; Shrestha, Sneha; Raj Niraula, Surya (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Introduction: Dental treatment of children is the most needed service that remains neglected because of a lack of skill to manage dental fear and anxiety (DFA). Both the non-pharmacological and pharmacological behavior management continuum should be followed to treat children. Objective: To assess and compare DFA levels in children before and after dental treatment using nitrous oxide-oxygen inhalation sedation (NOIS), to assess and compare the change in behavior in children undergoing NOIS, and to compare the level of DFA in children undergoing invasive and non-invasive dental treatment. Methods: DFA was measured using the Children’s Fear Survey Schedule Dental Subscale (CFSS-DS), Modified Child Dental Anxiety Scale (MCDAS), and Facial Image Scale (FIS) before and after the dental treatment under NOIS. The change in children’s behavior during invasive and noninvasive treatment under NOIS was assessed by Frankl Behavior Rating Scale (FBRS). Results: A significant reduction in DFA was seen within each cohort as measured by 3 scales: CFSS-DS, MCDAS, and FIS (P≤0.001). There was also a positive change in behavior of children during the time of dental treatment under NOIS as measured by FBRS. However, there was no significant difference between invasive and non-invasive treatment groups with regard to DFA. Conclusions: Minimal sedation provided by NOIS significantly reduced DFA in children, and there was a positive change in their behavior during the time of treatment. NOIS was effective in decreasing DFA in both invasive and non-invasive dental treatment.